Propiedades físico-químicas y nutricionales de los frutos de Jacaratia spinosa en remanentes de la selva paranaense, en Misiones, Argentina - Rauh, Anahi Tamara (2024)
Jacaratia spinosa (Aubl.) A. DC. is a dioecious tree species belonging to the Caricaceae family, naturally occurring in the Upper Paraná Atlantic Forest ecoregion. This tree is significant for the preservation of rain forest biodiversity and holds cultural, nutritional, pharmacological, and tourism potential. However, little is known about the morphological, physicochemical, and nutritional characteristics of its fruits. The objective of this study was to characterize the mature fruits of female J. spinosa individuals from various locations in the Misiones province, Argentina, to emphasize their importance in the food industry. Fifteen female individuals were identified and georeferenced across eight locations, with each individual considered as a separate treatment. Mature fruits were collected in four samples per plant, with 10 fruits each, for morphological (weight, length, diameter, skin and pulp color), physicochemical (pH, soluble solids, total acidity and ratio), nutritional (moisture, protein, ash content and minerals) analysis, and identification of natural pigments. Data were subjected to homogeneity and normality tests using the Shapiro-Wilk and Bartlett methods. When assumptions were not met, transformations such as square root (√(x+1)), logarithmic, or Box-Cox were applied. Transformed data were then analyzed by ANOVA, followed by mean comparison using the Scott-Knott test at a significance level of p<0.05. Additionally, multivariate analysis of yield components, fruit quality, ash composition, and bromatological analysis was performed using PCA. Significant differences in the morphological, physicochemical, and nutritional characteristics of mature fruits were found among the different individuals, as expected in a dioecious species. The groups formed by multivariate analysis did not correlate with the region of origin of the specimens, indicating no effect of isolation yet. Natural pigments were identified that can be utilized in the food industry, and extraction protocols were defined that optimize the quantity and quality of the extracted pigments.